2003
DOI: 10.1210/en.2002-221103
|View full text |Cite
|
Sign up to set email alerts
|

Developmental and Hormonal Signals Dramatically Alter the Localization and Abundance of Insulin Receptor Substrate Proteins in the Mammary Gland

Abstract: Insulin receptor substrates (IRS) are central integrators of hormone, cytokine, and growth factor signaling. IRS proteins can be phosphorylated by a number of signaling pathways critical to normal mammary gland development. Studies in transgenic mice that overexpress IGF-I in the mammary gland suggested that IRS expression is important in the regulation of normal postlactational mammary involution. The goal of these studies was to examine IRS expression in the mouse mammary gland and determine the importance o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(49 citation statements)
references
References 58 publications
2
47
0
Order By: Relevance
“…Taken together, the results support our hypothesis that IRS-1 and IRS-2 are important for normal lactation, but they also suggest that compensatory mechanisms within the secretory epithelium may prevent the appearance of a more dramatic phenotype in animals with a single deletion of either IRS-1 or IRS-2. The induction of IRS protein expression during the first few days of lactation is consistent with previous studies published in our laboratory which demonstrated higher levels of IRS protein expression during mid-lactation compared with late pregnancy (Lee et al 2003b). The immunoblot results in the current study extend that observation by demonstrating that this upregulation of IRS-1 and IRS-2 is an early event that is temporally linked with the process of secretory activation.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Taken together, the results support our hypothesis that IRS-1 and IRS-2 are important for normal lactation, but they also suggest that compensatory mechanisms within the secretory epithelium may prevent the appearance of a more dramatic phenotype in animals with a single deletion of either IRS-1 or IRS-2. The induction of IRS protein expression during the first few days of lactation is consistent with previous studies published in our laboratory which demonstrated higher levels of IRS protein expression during mid-lactation compared with late pregnancy (Lee et al 2003b). The immunoblot results in the current study extend that observation by demonstrating that this upregulation of IRS-1 and IRS-2 is an early event that is temporally linked with the process of secretory activation.…”
Section: Discussionsupporting
confidence: 93%
“…Our previous work showed that IRS-1 and IRS-2 levels were developmentally regulated in the mammary gland (Lee et al 2003b). Interestingly, the expression profile of IRSs was suggested to be similar to that of milk proteins such as b-casein and whey acidic protein (Rosen et al 1999), with increased expression during late pregnancy, dramatically elevated levels during lactation, and rapid loss of protein expression during involution.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…30,32,[42][43][44][45][46][47] Of the IRS family members, only IRS-1 and IRS-2 are expressed in normal mammary epithelial cells and in breast carcinoma cells. 32,[48][49][50] A limited number of studies have investigated IRS-1 expression in human tumors by immunohistochemistry and the results have been inconsistent. One study reported strong down-regulation of IRS-1 in Grade 3, poorly differentiated breast tumors, suggesting a positive correlation between low IRS-1 and poor prognosis.…”
Section: The Irs Proteins and Breast Cancermentioning
confidence: 99%
“…A role for IRS-1 in the cross-talk between the estrogen, insulin, and IGF-1 pathways has been shown in experimental studies. In mice, IRS-1 plays a role in mammary gland development and this function is regulated by steroid hormones, especially the combination of estrogen and progesterone [65]. In vitro studies [11,66,67] have found that estrogen, especially E 2 , can stimulate and increase the expression of IRS-1 protein levels in breast tumor cells resulting in enhanced insulin or IGF-1 signaling.…”
Section: Discussionmentioning
confidence: 99%